(untitled) (Web of Teachers: Inderscience Research, 2025)
Types of men’s jackets. Types of single-breasted, double-breasted jackets. Types of constructive methodologies. Calculation and construction of the base structure of the men’s jacket for the typical figure based on the size table and size values obtained from the body to build the base structure of the men’s jacket (SC).